Biomolecule-derived supported cobalt nanoparticles for hydrogenation of industrial olefins, natural oils and more in water. Issue 18 (29th August 2019) - Pews-Davtyan, Anahit; Scharnagl, Florian Korbinian; Hertrich, Maximilian Franz; Kreyenschulte, Carsten; Bartling, Stephan; Lund, Henrik; Jackstell, Ralf; Beller, Matthias
Abstract : Biomolecule modified supported cobalt nanoparticles efficiently hydrogenate diverse natural, industrial and functionalized olefins in water under mild conditions. Abstract : Catalytic hydrogenation of olefins using noble metal catalysts or pyrophoric RANEY® nickel is of high importance in the chemical industry. From the point of view of green and sustainable chemistry, design and development of Earth-abundant, less toxic, and more environmentally friendly catalysts are highly desirable. Herein, we report the convenient preparation of active cobalt catalysts and their application in hydrogenations of a wide range of terminal and internal carbon–carbon double bonds in water under mild conditions. Catalysts are prepared on multi-gram scale by pyrolysis of cobalt acetate and uracil, guanine, adenine orl -tryptophan. The most active material Co-Ura/C-600 showed good productivity in industrially relevant hydrogenation of diisobutene to isooctane and in natural oil hardening.